Mercury Accumulation in Marine Sediments – A Comparison of an Upwelling Area and Two Large River Mouths - Zaferani, Sara; Biester, Harald (Frontiers in Marine Science, 2021)
Understanding marine Hg biogeochemistry is crucial, as the consumption of Hg-enriched ocean fish is the most important pathway of Hg uptake in humans. Although ocean sediments are seen as the ultimate Hg sink, marine sediment studies on Hg accumulation are still rare. In this context, studying Hg behavior in the marine environment, especially in upwelling environments, is of particular interest due to its importance in these great upwelling regions for the global fishery. There are contradictory statements about the fate of Hg in upwelling regions. Some studies have suggested high biotic reduction of oxidized Hg and gaseous elemental mercury evasion to the atmosphere. More recent work has suggested that in upwelling regions, where productivity is high, evasion of gaseous elemental mercury is diminished due to scavenging and sedimentation of Hg by organic particles. In this study, we compared Hg concentrations and accumulation rates derived from sediment cores collected in the Peruvian upwelling region and compared them with those of two other cores collected from the sediment fan of the Amazon and a core from the Congo Basin, which is influenced by both seasonal coastal upwelling and discharge from the river. Median Hg concentrations were higher at the Peru Margin (90.7 µg kg−1) and in the Congo Basin (93.4 µg kg−1) than in the Amazon Fan (35.8 µg kg−1). The average Hg accumulation rates in sediments from the Peru Margin (178 µg m-2 yr-1) were factors of ∼ 4 and 39 times higher than those from the Congo Basin and Amazon Fan, respectively. PCA of the geochemical data set reveals that Amazon Fan sediments are strongly influenced by the deposition of terrestrial material, which is of less importance in the Congo Basin and of minor importance in Peru Margin sediments. Accordingly, Hg export to sediments in upwelling areas largely surpasses that in fans of large rivers that drain large terrestrial catchments. The high Hg accumulation rates in the sediments from the upwelling area and the minor influence of terrestrial Hg fluxes there suggest that atmospheric-derived Hg in upwelling areas is effectively exported to the sediments through scavenging by organic particles.